Upper and Lower Body Muscle Power Increases After 3-Month Resistance Training in Overweight and Obese Men. (November 2017) - Zemková, Erika; Kyselovičová, Oľga; Jeleň, Michal; Kováčiková, Zuzana; Ollé, Gábor; Štefániková, Gabriela; Vilman, Tomáš; Baláž, Miroslav; Kurdiová, Timea; Ukropec, Jozef; Ukropcová, Barbara
This study evaluates the effect of 3 months resistance and aerobic training on muscle strength and power in 17 male overweight and obese men. Subjects underwent either a resistance or aerobic training for a period of 3 months (three sessions per week). Peak isometric force, rate of force development, peak power and height of countermovement and squat jumps, reactive strength index, and mean power in the concentric phase of bench presses were all assessed prior to and after completing the training program. Results identified a significant increase of mean power during both countermovement bench presses at 30 kg (18.6%, p = .021), 40 kg (14.6%, p = .033), and 50 kg (13.1%, p = .042) and concentric-only bench presses at 30 kg (19.6%, p = .017) and 40 kg (13.9%, p = .037) after the resistance training. There was also a significant increase in the height of the jump (12.8%, p = .013), peak power (10.1%, p = .026), and peak velocity (9.7%, p = .037) during the countermovement jump and height of the jump (11.8%, p = .019), peak power (9.6%, p = .032), and peak velocity (9.5%, p = .040) during the squat jump. There were no significant changes in the reactive strength index, peak force, and the rate of force development after the resistance training. The aerobic group failed to show any significant improvements in these parameters. It may be concluded that 3 months of resistance training without caloric restriction enhances upper and lower body muscle power in overweight and obese men.